2019
DOI: 10.1021/acsaelm.9b00544
|View full text |Cite
|
Sign up to set email alerts
|

Highly Robust Flexible Vertical-Channel Thin-Film Transistors Using Atomic-Layer-Deposited Oxide Channels and Zeocoat Spacers on Ultrathin Polyimide Substrates

Abstract: Mechanically flexible vertical-channel-structured thin-film transistors (VTFTs) with a channel length of 200 nm were fabricated on 1.2 μm thick colorless polyimide (CPI) substrates. All layers composing the gate stacks were prepared by atomic-layer deposition (ALD) with a good step coverage, and the process thermal budget was designed below 180 °C. Zeocoat was introduced as a spacer material to improve the device characteristics by properly determining the process conditions for clearly forming the vertical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…Notably, even though this mobility is the first reported value for a vertical transistor using a p-type oxide channel, the technical level for electrical performance is outstanding and even comparable to n-type vertical transistors. 18,22,39 In addition, it should be noted that the SS and on/off current ratio are preferably better than those from previously reported planar p-type transistors (Table S1, ESI †) and vertical n-type transistors. 40,41 The channel coating process provides extraordinarily good electrodeposition, and existing methods, such as conventional sputtering and sol-gel processes, cannot produce artificially vertically aligned GBs in the oxide channel layers.…”
Section: Electrical Properties Of the Sb Doped Cu 2 O Vertical Transi...mentioning
confidence: 68%
See 1 more Smart Citation
“…Notably, even though this mobility is the first reported value for a vertical transistor using a p-type oxide channel, the technical level for electrical performance is outstanding and even comparable to n-type vertical transistors. 18,22,39 In addition, it should be noted that the SS and on/off current ratio are preferably better than those from previously reported planar p-type transistors (Table S1, ESI †) and vertical n-type transistors. 40,41 The channel coating process provides extraordinarily good electrodeposition, and existing methods, such as conventional sputtering and sol-gel processes, cannot produce artificially vertically aligned GBs in the oxide channel layers.…”
Section: Electrical Properties Of the Sb Doped Cu 2 O Vertical Transi...mentioning
confidence: 68%
“…21 For instance, Yoon et al reported flexible vertical oxide transistors with a combination of atomic layer deposited (ALD) IGZO channels and Zeocoat spacer layers showing good positive bias stress (PBS) and negative bias stress (NBS) behaviors. 22 Consequently, the choice of adequate spacer materials and optimization of the process for definition of the vertical channel with regards to the dry etching of spacer layers has been seriously considered. Nevertheless, to the best of our knowledge, there are still no reports of vertical thin-film transistors fabricated from p-type oxide materials, regardless of the preparation method and performance level.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances can be divided into two approaches. One is to exploit the full potential of TFTs with ALD‐derived n ‐channel oxide channels to verify the feasibility of using them as non‐planar structures such as vertical TFT (VTFT) 72–75 in AR/VR displays or three‐dimensional NAND flash memory. The other combines LTPS‐compatible high‐performance TFTs with an ALD‐derived n ‐type semiconducting channel layer through novel structures including heterostructures, 22–25 bilayers, 26 and hybrid channels 27,28 …”
Section: Ald‐derived N‐channel Oxide Tftsmentioning
confidence: 99%
“…The feasibility of VTFTs with an ALD‐derived IGZO channel layer on an ultra‐thin polyimide substrate was examined by Kim et al 73 The fabricated VTFTs consisted of sputtered ITO electrodes, a spin‐coated Zeocoat spacer, an ALD‐derived IGZO channel, and an Al 2 O 3 gate insulator (Figure 8A). The combination achieved reasonable electrical performance, with a μ FE of 6.6 cm 2 /Vs, a V TH of 1.52 V, an SS of 0.34 V/dec, and an I ON/OFF of 5.2 × 10 5 by adopting a Zeocoat spacer to ensure a smooth and clear surface for the vertical side wall (Figure 8B).…”
Section: Ald‐derived N‐channel Oxide Tftsmentioning
confidence: 99%
See 1 more Smart Citation